Pengendalian dan pencegahan hipertensi melalui pengenalan Dietary Approach to Stop Hypertention (DASH) dengan pemanfaatan buku saku dan media daring - Utama, Feranita; Ningsih, Windi Indah Fajar; Sari, Desri Maulina (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Hypertension is a non-communicable disease (NCD) and becomes health problem often found among employees. Somebody who spent time in the office for approximately eight hours in five working days, did not do regular exercise due to no time to exercise and ate foods that were not in accordance with the guidelines for balanced nutrition so that it leads to the risk of hypertension. The problem-solving framework used in this activity was to provide education related to the management and precaution of hypertension through the introduction of a DASH diet with the used of pocket books and online Whatsapp group media for employees at Sriwijaya University. In general, education and introduction to the DASH diet were considered quite successful. As many as 30 participants involved but 24 fulled fill the pretest and only 20 finished post -test. This community service activity was expected that the community will be able to recognize and apply the concept of the DASH diet that can control and prevent hypertension.